Stalinism : Russian and Western views at the turn of the millennium - Litvin, Alter L.; Keep, John L. H. (London ; New York : Routledge, 2005)
Stalinism surveys the efforts made in recent years by professional historians, in Russia and the West, to better understand what really went on in the USSR between 1929 and 1953.
Sources -- Stalin's biography -- Assessing Stalin's role as leader -- Terror -- Foreign policy -- Old controversies, new findings -- "A peculiar new state" : politics and government -- Adventures in social history : peasants and workers -- "It's a woman's world" : gender studies and daily life -- Captive minds : faith, science, history -- "Koba the dread" : repression and terror -- No longer a riddle? : aspects of Soviet foreign policy.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Stalin, Joseph, -- 1878-1953.; Stalin, Joseph, -- 1879-1953.; Stalin, Joseph, -- 1878-1953; Soviet Union -- History -- 1925-1953.; URSS -- Histoire -- 1925-1953.; HISTORY; Soviet Union -- History -- 1925-1953.; Soviet Union; Russia & Former Soviet Republics; Regions & Countries - Europe; History & Archaeology; 1925-1953; History